Penerapan Hukum Darurat Militer Saat Konflik Gerakan Aceh Merdeka - Yohana Sekar Pawening; Irwan Triadi (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
The emergence of the resistance movement, of course, because there are factors that influence it. The birth of DI/TII in Aceh was caused by the central government's policy to merge Aceh province into North Sumatra province on August 8, 1950. This paper will explain the application of emergency military law. Specifically during the conflict that occurred in the Aceh region which led to the formation of the Free Aceh Movement from 1976 to 2005. By using normative legal research methods. The trigger for the proclamation of Aceh's independence was the exploitation of Aceh's natural resources during the Soeharto era, where petroleum and natural gas were managed by Exxon Mobil Oil Indonesia which caused regional sentiment, that all Aceh's wealth was sent to Jakarta, even Hasan Tiro once said Aceh should have the advantage of its natural resources like Brunei Darussalam. The Presidential Decree (Keppres) to launch a massive military operation in Aceh had been drafted long before, after cabinet meetings held at the Palace, as well as through the deliberations of the people's representatives in Senayan, Jakarta in early 2003. The aim was to crush the Free Aceh Movement (GAM). The Helsinki MOU is one of the negotiations carried out between the Government of the Republic of Indonesia and the Free Aceh Movement held in Helsinki, Finland, August 15, 2005 creating a new system and method of relations between the central government and the Aceh government, which is fully supported by the international community.